(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
A specific and sensitive reverse phase high pressure liquide chromatography (RP-HPLC) and ultra-performance liquide chromatography (UPLC) method for the determination of related substances for fixed-dose combination formulation of Amlodipine Besylate, Hydrochlorothiazide and Olmesartan Medoxomil was developed and validated. By using the gradient RP-HPLC method, a total of 25 known and unknown impurities related to Amlodipine Besylate, Hydrochlorothiazide and Olmesartan Medoxomil in combination formulation were separated and quantified in the linearity range of (0.2 to 3.0 μg/mL) for Amlodipine Besylate, (0.5 to 7.5 μg/mL) for Hydrochlorothiazide and (0.8 to 12.0 μg/mL) for Olmesartan Medoxomil with good squared correlation (>0.99). The recovery study was established from LOQ (0.05%) to 150% of the specification limit. A precision study was performed by spiking each known impurities at the specification level. In this study, two separate analytical methods RP-HPLC and UPLC have been developed, validated, and compare for the simultaneous quantification of Amlodipine Besylate, Hydrochlorothiazide, and Olmesartan Medoxomil tablets with their impurities. In these methods total of 28 peaks were separated in 70 minutes run time by HPLC method while in 45 minutes by UPLC method. Both the methods are developed with high selectivity, sensitivity, and robustness to separate 28 peaks in a single method. The proposed methods have a high degree of sensitivity and will provide fast and cost-effective quantitative control of Pharmaceutical formulations.